2014
DOI: 10.1007/s11259-013-9587-5
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinductivity of gelatin/β-tricalcium phosphate sponges loaded with different concentrations of mesenchymal stem cells and bone morphogenetic protein-2 in an equine bone defect model

Abstract: Fracture is one of the most life-threatening injuries in horses. Fracture repair is often associated with unsatisfactory outcomes and is associated with a high incidence of complications. This study aimed to evaluate the osteogenic effects of gelatin/β-tricalcium phosphate (GT) sponges loaded with different concentrations/ratios of mesenchymal stem cells (MSCs) and bone morphogenetic protein-2 (BMP-2) in an equine bone defect model. Seven thoroughbred horses were used in this study. Eight bone defects were cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…Tsuzuki et al (2012) demonstrated that rhBMP-2/b-TCP sponges could significantly enhance bone regeneration as compared to either component alone. Moreover, significant improvements in the healing of surgically induced bone and osteochondral defects were demonstrated following treatment with rhBMP-2/b-TCP sponges in combination with MSCs (Seo et al 2014), or with MSCs and platelet rich plasma , Seo et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsuzuki et al (2012) demonstrated that rhBMP-2/b-TCP sponges could significantly enhance bone regeneration as compared to either component alone. Moreover, significant improvements in the healing of surgically induced bone and osteochondral defects were demonstrated following treatment with rhBMP-2/b-TCP sponges in combination with MSCs (Seo et al 2014), or with MSCs and platelet rich plasma , Seo et al…”
Section: Discussionmentioning
confidence: 99%
“…Due to its osteoinductive effects (Devescovi et al 2008), it is approved as an alternative for cancellous bone grafts in humans in special indications (Govender et al 2002, Mont et al 2004. Previous studies demonstrated that recombinant human BMP-2 (rhBMP-2) loaded scaffolds accelerated bone regeneration in equine bone defect models (Perrier et al 2008, Seo et al 2014. Gelatin b-tricalcium phosphate (b-TCP) sponges loaded with rhBMP-2 also enhanced healing of osteochondral defects in horses , Seo et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Although the combination of gelatin and β-tricalcium phosphate has already been used as a biomaterial 8,9) , some issues, such as material safety and its properties remain to be solved. The G-TCP membranes were developed with the concept to apply not for big bone defects such as the critical-sized defects, but for smaller bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is based on the concept that application of a membrane creates a protected space which facilitates the proliferation of angiogenic and osteogenic cells from the basal bone without interference from proliferating fibroblasts in the surrounding soft tissue 5) . To develop an ideal bioresorbable membrane for GBR, we chose gelatin because it has been used as a carrier of recombinant proteins, such as fibroblast growth factors (FGFs) and bone morphogenetic proteins (BMPs) [6][7][8][9] , and lacks antigenicity 10) . However, a membrane prepared from gelatin alone cannot function as a GBR membrane due to its mechanical weakness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation